ECOLOGY OF RIVER BASIN MOLLUSCS" MOYLISUV" (American Journal of Pedagogical and Educational Research, 2024)
The Moylisuv River Basin is located in the southern part of Uzbekistan and is characterized by its unique biodiversity and ecosystem. This basin is important not only for water resources, but also for a wide variety of flora and fauna. The basin-dwelling molluscs, specifically Bivalvia (bivalve molluscs) and Gastropoda (twisting molluscs) species, fulfill important roles in the ecosystem.